Ethanol intoxication prolongs post‐burn pulmonary inflammation: role of alveolar macrophages. Issue 5 (16th August 2016) - Shults, Jill A.; Curtis, Brenda J.; Boe, Devin M.; Ramirez, Luis; Kovacs, Elizabeth J.
Abstract : Amplified pulmonary inflammation following intoxication and burn injury is driven by AM cell death, and a heightened pro‐inflammatory profile. Abstract : In this study, the role and fate of AMs were examined in pulmonary inflammation after intoxication and injury. Clinical evidence has revealed that half of all burn patients brought to the emergency department are intoxicated at the time of injury. This combined insult results in amplified neutrophil accumulation and pulmonary edema, with an increased risk of lung failure and mortality, relative to either insult alone. We believe that this excessive pulmonary inflammation, which also parallels decreased lung function, is mediated in part by AMs. Restoration of lung tissue homeostasis is dependent on the eradication of neutrophils and removal of apoptotic cells, both major functions of AMs. Thirty minutes after binge ethanol intoxication, mice were anesthetized and given a 15% total body surface area dorsal scald injury. At 24 h, we found a 50% decrease in the total number of AMs ( P < 0.05) and observed a proinflammatory phenotype on the remaining lung AMs. Loss of AMs paralleled a 6‐fold increase in the number of TUNEL + lung apoptotic cells ( P < 0.05) and a 3.5‐fold increase in the percentage of annexin V + apoptotic cells in BAL ( P < 0.05), after intoxication and injury, relative to controls. In contrast to the reduction in the number of cells, AMs from intoxicated and injured mice had a 4‐fold increase in efferocytosis ( P < 0.05). In summary, these data suggest that loss of AMs may delay resolution of inflammation, resulting in the pulmonary complications and elevated mortality rates observed in intoxicated and burn‐injured patients.